2013
DOI: 10.1371/journal.pone.0083248
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxygen Depletion Is Independent of Dive Function in a Deep Diving Vertebrate, the Northern Elephant Seal

Abstract: Although energetics is fundamental to animal ecology, traditional methods of determining metabolic rate are neither direct nor instantaneous. Recently, continuous blood oxygen (O2) measurements were used to assess energy expenditure in diving elephant seals (Mirounga angustirostris), demonstrating that an exceptional hypoxemic tolerance and exquisite management of blood O2 stores underlie the extraordinary diving capability of this consummate diver. As the detailed relationship of energy expenditure and dive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Our suggestion is supported by the previous finding that blood oxygen stores are depleted to a similar level during diving in elephant seals, irrespective of dive type (i.e. foraging dives and drift dives; Meir et al, 2013).…”
Section: Functional Implicationssupporting
confidence: 89%
“…Our suggestion is supported by the previous finding that blood oxygen stores are depleted to a similar level during diving in elephant seals, irrespective of dive type (i.e. foraging dives and drift dives; Meir et al, 2013).…”
Section: Functional Implicationssupporting
confidence: 89%
“…In other diving homeotherms, activity does not correlate well with energy expenditure (Fahlman et al, 2008;Halsey et al, 2011;Meir et al, 2013;Volpov et al, 2015). We argue that in addition to mechanical activity, dive costs are strongly affected by the suppression of oxygen consumption via reduced heart rate, body temperature, shunting of blood past non-vital organs and other mechanisms, and that physiology, in addition to physics, plays an important role in oxygen consumption during dives.…”
Section: Discussion Bioenergetic Insights Offered By Dbamentioning
confidence: 75%
“…The same exponential model improves estimation of dive costs in auks (Elliott et al, 2013b). Several authors have observed that activity does not predict energy consumption during diving by homeotherms (Halsey et al, 2011;Meir et al, 2013); one possible explanation for this is that activity costs are overwhelmed by hypometabolism. Evidence for such hypometabolism has been observed in other cormorant species (Bevan et al, 1997).…”
Section: Statistical Analysesmentioning
confidence: 91%
See 1 more Smart Citation
“…emperor penguins, Aptenodytes forsteri; rhinoceros auklets, Cerorhinca monocerata; Weddell seals, Leptonychotes weddelli; northern elephant seals, Mirounga angustirostris; etc. (Burns, 1999;Hassrick et al, 2013;Meir et al, 2013;Ponganis et al, 2011;Yamamoto et al, 2011)], or on the diving behavior of specific species with restricted distributions [e.g. Australian sea lion, Neophoca cinerea (Fowler et al, 2007); New Zealand sea lion, Phocarctos hookeri (Costa et al, 1998;Leung et al, 2014); Galapagos sea lion, Zalophus wollabaecki (Villegas-Amtmann and ].…”
Section: Introductionmentioning
confidence: 99%